2006
DOI: 10.3892/ijo.29.2.349
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal cathepsin initiates apoptosis, which is regulated by photodamage to Bcl-2 at mitochondria in photodynamic therapy using a novel photosensitizer, ATX-s10 (Na)

Abstract: Abstract. ATX-s10 is a novel and second-generation photosensitizer for photodynamic therapy (PDT). In order to conduct clinical trials of ATX-s10-PDT and/or extend its clinical applications, it is very important to elucidate the mechanisms of the action of ATX-s10-PDT. We examined the apoptic response against ATX-s10-PDT using a Bcl-2 or Bcl-2 mutant overexpressing cells. Using fluorescent microscopy, ATX-s10 localized not only to mitochondria but also to lysosomes and possibly other intracellular organelles, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 21 publications
5
38
1
1
Order By: Relevance
“…Bcl-2, an antiapoptotic protein of the Bcl-2 family, promotes cell survival by interfering with the activation of the cytochrome c/Apaf-1 pathway through stabilization of the mitochondrial membrane (26) and is a target of some photosensitizers (27)(28)(29)(30). In the present study, Bcl-2 was down-regulated by 9-HPbD-PDT, which was prevented by pretreatment with the antioxidants (Fig.…”
Section: Discussionsupporting
confidence: 54%
“…Bcl-2, an antiapoptotic protein of the Bcl-2 family, promotes cell survival by interfering with the activation of the cytochrome c/Apaf-1 pathway through stabilization of the mitochondrial membrane (26) and is a target of some photosensitizers (27)(28)(29)(30). In the present study, Bcl-2 was down-regulated by 9-HPbD-PDT, which was prevented by pretreatment with the antioxidants (Fig.…”
Section: Discussionsupporting
confidence: 54%
“…Photodynamic therapy with photosensitizers that accumulate inside lysosomes may induce cell death dependent on LMP and cathepsins (Buytaert et al, 2007), as has been shown for ATX-s10 and N-aspartyl chlorin e6 (Caruso et al, 2004;Ichinose et al, 2006). In addition, antiapoptotic members of the Bcl-2 family of proteins are often degraded after photodynamic therapy, making cells more sensitive to apoptotic cell death (Xue et al, 2003;Ichinose et al, 2006).…”
Section: Lmp In Cancer Cellsmentioning
confidence: 99%
“…Aliquots of the cells were seeded into 25 cm 2 flasks in amounts sufficient to yield 50-150 colonies. After incubation for 10-14 days, the cells were stained with 0.1% crystal violet in 20% ethanol, and colonies containing at ≥50 cells were counted (13,23,24). The plating efficiency of the untreated cells was 30-40%.…”
Section: Methodsmentioning
confidence: 99%